Persistent mullerian duct syndrome with testicular seminoma in transverse testicular ectopia - Sharada R Rane; Deepak Pandurang Dangmali; Sharvari D Vishwasrao; Shaila C Puranik (Wolters Kluwer Medknow Publications, 2018)
Persistent Mullerian Duct Syndrome (PMDS) is a disorder of male pseudohermaphroditism characterized by the persistence of Mullerian duct derivatives (uterus, fallopian tubes, and upper two-third of vagina) in a phenotypically and genotypically male. Transverse testicular ectopia (TTE) is a rare congenital anomaly in which both gonads migrate toward same hemiscrotum. About 150 cases of PMDS and 100 cases of TTE have been reported in previous studies. Testicular tumor in patients with PMDS with TTE is very rare. We report a case of testicular seminoma in a 35-year-old male patient with PMDS and TTE. Preoperative diagnosis was not possible in most of the reported cases.